2012
DOI: 10.1002/jbmr.1713
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor (AR) in osteocytes is important for the maintenance of male skeletal integrity: Evidence from targeted AR disruption in mouse osteocytes

Abstract: Androgens play a key role in the maintenance of male skeletal integrity. The regulation of this integrity by androgen receptor (AR) signaling has been mainly attributed to osteoblasts. Although osteocytes have emerged as key regulators of bone remodeling, the influence of sex steroids on these cells has been poorly studied. We aimed to investigate the role of AR signaling, specifically in osteocytes using the Cre/LoxP system in male mice (driven by dentin matrix protein 1 [ocy-ARKOs]). Osteocyte fractions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 36 publications
8
82
1
2
Order By: Relevance
“…The main finding in the present study is that ERα in osteocytes is important for trabecular bone formation in male mice. In this study we used the Dmp1-Cre mouse model, which is a widely used and well-described mouse model for deleting gene expression in osteocytes (25,26). We confirmed the specificity of the Dmp1-Cre mouse model using ROSA26-Cre reporter mice, demonstrating specific recombination in osteocytes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The main finding in the present study is that ERα in osteocytes is important for trabecular bone formation in male mice. In this study we used the Dmp1-Cre mouse model, which is a widely used and well-described mouse model for deleting gene expression in osteocytes (25,26). We confirmed the specificity of the Dmp1-Cre mouse model using ROSA26-Cre reporter mice, demonstrating specific recombination in osteocytes.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have shown that the Dmp1-Cre mouse strain has the capacity to specifically inactivate loxP flanked genes in osteocytes expressing CRE-recombinase selectively in osteocytes under the control of a 10-kb promoter fragment of the osteocytic Dmp1 marker gene (25,26). To validate that the Dmp1-Cre mouse strain has the capacity to specifically recombine DNA in osteocytes postnatally, we mated Dmp1-Cre mice with ROSA26-Cre reporter mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, even small changes, effected over a long period of time, can lead to an altered phenotype, such as the decreased trabecular bone volume observed in 6-month-old female mice. In the recent study by Sinnesael et al, 21 osteocytic AR expression was found to be pivotal for the maintenance of trabecular, but not cortical, bone volume in male mice upon aging. 21 Our study shows that the AR is also involved in the maintenance of trabecular bone volume of female mice.…”
Section: Discussionmentioning
confidence: 90%
“…In the recent study by Sinnesael et al, 21 osteocytic AR expression was found to be pivotal for the maintenance of trabecular, but not cortical, bone volume in male mice upon aging. 21 Our study shows that the AR is also involved in the maintenance of trabecular bone volume of female mice. This result has to be viewed in the light that although low levels of testosterone have been reported in fetal 23 and neonate 24 female mice, the serum testosterone concentration in adult female mice is actually 10-fold higher than the estradiol concentration, 25 which suggests that testosterone can act as a ligand, driving AR-mediated effects in the trabecular bone maintenance of female mice.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation